The surfer`s shoulder: A systematic review of current literature and potential pathophysiological explanations of chronic shoulder complaints in wave surfers - Langenberg, L. C.; Vieira Lima, G.; Heitkamp, S. E.; Kemps, F. L. A. M.; Jones, M. S.; de Almeida Garcia Moreira, M. A.; Eygendaal, D. (Sports Medicine - Open, 2021)
Background: Wave surfing will debut in the next Olympic Games and is increasingly popular as a sport. Chronic shoulder complaints are frequently reported amongst surfers, though literature researching its pathophysiology and prevention is scarce. This article provides an overview of the current literature, proposes a potential pathogenesis and a potential physiotherapeutic prevention program for surf-induced shoulder complaints. Methods: A systematic review was performed considering the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for articles regarding kinematic analysis of the surf paddling movement. Data sources were Embase, MEDLINE (PubMed) and Research gate. We included case series and cohort studies that originally studied or described the paddle movement made by wave surfers, studies that reported on kinesiologic analysis with nerve conduction studies and studies on 3D motion analysis of the shoulder while paddling. Results: Eight original articles were included that analysed the shoulder movement in paddling surfers. Muscles that are active during paddling are mainly internal rotators and muscles that are involved in shoulder flexion. Internal rotators are active in propelling the surfer through the water, though external rotator strength is only used while the arm is out of the water. Discussion: In surfers with shoulder complaints, external rotation range of motion and external rotation strength are impaired. Scapulothoracic dyskinesis may occur and subacromial pain syndrome may coincide. Further research should address potential pectoralis minor shortening, which may lead to aberrant scapular tilt and lateral rotation of the scapula. The surfer`s shoulder is characterised by external rotation deficit, as opposed to internal rotation deficit in the thrower`s shoulder, and it differs substantially from shoulder complaints in swimmers. Therefore, a specific prevention or rehabilitation protocol for surfers is required. Decreased thoracic extension may thereby alter the risk of scapular dyskinesis and hence increase the risk of impingement around the shoulder joint. A potential physiotherapeutic prevention programme should address all these aspects, with the main goal being to increase external rotator strength and to stretch the internal rotators. Conclusion: There is a high incidence of chronic surf-induced shoulder complaints in surfers. Symptoms may arise due to imbalanced training or scapular dyskinesis, which may subsequently trigger subacromial pain. Physiotherapeutic prevention should include stretching of the internal rotators, external rotator training and optimisation of thoracic extension and scapulothoracic movement.